This is not a book - "Picard, Michael" (London, 2007)
"This is Not a Book" will stretch your mind, put your neurons through their paces, and challenge the foundations of your opinions and knowledge itself. You'll discover you can't even trust your own senses - even though they may be all you have. Packed with philosophical puzzles that have intrigued the greatest minds, quizzes that reveal the inconsistencies of our ideas, insoluble logical paradoxes, and moral dilemmas that force us to confront the consequences of our beliefs, "This is Not a Book" will give your intellect a workout that you'll thoroughly enjoy.This book is divided into four sections, one for each of the major branches of philosophy. Each section includes an overview of the subject and brief profiles of the philosophers whose work has influenced thinking in that area, together with quizzes, games, mental exercises, and thought experiments in which you are asked to take on a particular view of reality and follow where it leads. This is the ideal introduction for anyone coming to this fascinating subject for the first time.
Keywords: Western philosophy